Topic: Formation of Diminutives in English and Swahili Languages : A contrastive Analysis - KANDOLO , Ass Modeste (IJRDO- Journal of Educational Research, 2021)
The present paper focuses on the formation of Diminutives in English and Swahili languages: a contrastive analysis. From the preceding discussion, it becomes clear that the diminutive forms in English can be produced either by suffixation or prefixation where only some parts of speech are included to express some affective meanings. On the other hand, these forms in Swahili are partially produced by prefixation where many parts of speech are involved to express, to a large extent, many other meanings besides smallness.